Penerapan Model Pembelajaran Discovery Learning Berbentuan Geogebra Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa SMP - M. Tata Aulia Rahman; Sri Andayani; Farizal Ramadhan (Mandalika Mathematics and Educations Journal, 2026)
This study was motivated by the low level of creative thinking skills among junior high school students in the subject of flat-sided solid geometry and the dominance of conventional learning methods that do not encourage concept exploration. This study aims to describe the application of the GeoGebra-assisted Discovery Learning model and examine the improvement in students' creative thinking skills. This research employed a classroom action research design through the stages of planning, action, observation, and reflection. The research subjects were eighth-grade junior high school students. The instruments used included a creative thinking ability test, observation sheets, and documentation. The results showed an increase in creative thinking skills in each cycle, as indicated by improvements in the indicators of fluency, flexibility, originality, and elaboration. Learning became more interactive, students were more active in exploring concepts, and were able to find various problem-solving strategies. Theoretically, these results reinforce the constructivist paradigm that mathematical creativity develops through structured exploration and discovery. Practically, this model can be an alternative for learning spatial geometry by paying attention to time management and optimal syntax implementation.